Attenuation of heart-rate variability in postmenopausal women on progestin-containing hormone replacement therapy - Christ, Michael; Seyffart, Karen; Wehling, Martin (The lancet, 1999)
The effect of total sleep deprivation on heart rate variability (HRV) in groups of postmenopausal women on oral hormone therapy (HT) (on-HT, n = 10, 64.2 (1.4) years), postmenopausal women without HT (off-HT, n = 10, 64.6 (1.4) years) and young women (n = 11, 23.1 (0.5) years) was studied using a prospective case-control setup. - Polysomnography was performed over an adaptation night, a baseline night, and a recovery night after 40 h of total sleep deprivation. Time and frequency domain and nonlinear HRV from overnight electrocardiogram recordings were compared between groups during baseline and recovery nights. Further, the changes in HRV from baseline to recovery were analysed and compared between groups. Finally, correlations of HRV to percentages of sleep stages and measures of sleep fragmentation were analysed during baseline and recovery. - Young women had higher HRV than older women; the most marked difference was between young and on-HT postmenopausal women. Sleep deprivation induced a decrease in frequency domain HRV in young and in off-HT women, an increase in α2 in off-HT women, and an increase in mean heart rate in on-HT women. The sleep deprivation effect was mainly uncorrelated to changes in sleep parameters. - Acute total sleep deprivation has a deleterious effect on the autonomic nervous system in young women, but an even more pronounced effect in postmenopausal women. Hormone therapy use in late postmenopause does not give protection against these changes. These harmful effects may partly explain the increased cardiovascular morbidity and overall mortality associated with sleep loss. - Heart rate variability and baroreceptor sensitivity are measures of autonomic control. While progestagen-containing replacement therapy in postmenopausal women adversely affects autonomic balance, the impact of hormonal contraceptives with synthetic progestagens on autonomic activity, neurohormones and C-reactive protein levels is not well characterized. - We analyzed parameters of heart rate variability and baroreceptor sensitivity in young healthy females without (n = 27) or on oral contraceptives with synthetic progestagens (n = 31). Demographic characteristics were not different among the examined groups. Total power (controls: 5682 ± 3618 vs. hormones: 4800 ± 2957 ms2; NS), standard deviation of beat-to-beat intervals (SDNN; 66 ± 24 vs. 63 ± 20 ms; p = 0.74), other time- and frequency-dependent parameters of heart rate variability and baroreceptor sensitivity (6.0 ± 3.2 vs. 6.5 ± 2.7 ms/mm Hg; NS) were not significantly different among the groups. Total cholesterol and triglyceride as well as C-reactive protein (CRP) levels were significantly higher in users of hormonal contraceptives than in non-users (cholesterol: 187 ± 37 vs. 166 ± 28 mg/dL; p = 0.05; triglycerides: 110 ± 35 vs. 68 ± 30 mg/dL; p = 0.01; CRP: 2.7 ± 2.1 vs. 1.0 ± 1.4 mg/L; p < 0.001). Heart rate variability, baroreceptor sensitivity, lipid parameters and CRP levels were not affected during the ovarian cycle in non-users of hormonal contraception. - The use of oral contraceptives containing synthetic progestagens was not associated with a modulation of autonomic tone, while lipid parameters and CRP levels were adversely affected. These data suggest that synthetic progestagens in modern oral contraceptives do not modulate the autonomic balance, but probably affect the atherogenic risk profile of young females in reproductive age. - Background: The aim of the study was to investigate the effects of a long term (1 year) hormone replacement therapy (HRT) on QT interval, QT dispersion (QTd) frequencies of arrhythmia and heart rate variability (HRV) parameters. Methods: Forty-six healthy postmenopausal women (mean age; 55.34±4.21) as a hormone replacement therapy group and 25 healthy premenopausal women (mean age; 35.36±6.06) as a control group were prospectively enrolled to the study. Hormone replacement therapy group was divided into two groups; estrogen replacement therapy (ERT) group (n=23) and progestin-estrogen replacement therapy (PERT) group (n=23). Standard 12 lead electrocardiograms and 24-h ambulatory Holter recording were obtained to evaluate the effects of one year of ERT and PERT on QT intervals, QTd, frequencies of arrhytmias and HRV parameters. Results: Long term use of ERT increases QT interval, QTd, in the frequencies of arrhytmia and HRV indexes of parasympathetic activity; however, the increase in frequencies of arrhythmia was not statistically significant (p>0.05). Long term use of PERT did not effected QT interval, QTd, frequencies of ventricular arrhythmia and HRV parameters (p>0.05).Frequency of supraventricular tachycardia increased in post-treatment PERT group was compared with pre-treatment PERT group. Conclusion: These findings supported the hypothesis that estrogen may directly modulate ventricular repolarization. But progestin do not effect the ventricular repolarization. However, these findings must be supported with a large-scale study. - The various mechanisms that may explain the association between brain dysfunction and the pathogenesis of metabolic syndrome (MS) leading to cardiovascular disease and type 2 diabetes have been reviewed. A Medline search was conducted until September 2003, and articles published in various national and international journals were reviewed. Experts working in the field were also consulted. Compelling evidence was found that saturated and total fat and low dietary n-3 fatty acids and other long-chain polyunsaturated fatty acids (PUFAs) in conjunction with sedentary behavior and mental stress combined with various personality traits can enhance sympathetic activity and increase the secretion of catecholamine, cortisol and serotonin, all of which appear to be underlying mechanisms involved in MS. Excess secretion of these neurotransmitters in conjunction with underlying long-chain PUFA deficiency may damage the neurons in the ventromedial hypothalamus and insulin receptors in the brain, in particular during fetal life, infancy and childhood, and lead to their dysfunction. Since 30-50% of the fatty acids in the brain are long-chain PUFAs, especially omega-3 fatty acids which are incorporated in the cell membrane phospholipids, it is possible that their supplementation may have a protective effect. Omega-3 fatty acids are also known to enhance parasympathetic activity and to increase the secretion of anti-inflammatory cytokines as well as acetylecholine in the hippocampus. It is possible that a marginal deficiency of long-chain PUFAs, especially n-3 fatty acids, due to poor dietary intake during the critical period of brain growth and development in the fetus, and later in the infant and also possibly in the child, adolescent and adult may enhance the release of tumor necrosis factor-alpha (TNF-α) interleukin (IL)-1, 2 and 6 and cause neuronal dysfunction. Experimental studies indicate that ventromedial hypothalamic lesions in rats induce hyperphagia, resulting in glucose intolerance and insulin resistance. Treatment with neuropeptide Y abolished hyperphagia and ob mRNA (leptin mRNA) in this animal model. Long-term infusion of norepinephrine and serotonin into the ventromedial hypothalamus impaired pancreatic islet function inasmuch as ventromedial hypothalamic norepinephrine and serotonin levels were elevated in hyperinsulinemic and insulin-resistant animals. Treatment with insulin was associated with restoration of hypothalamic neurotransmitter abnormalities, indicating that ventromedial hypothalamus dysfunction can impair pancreatic beta cells resulting in metabolic abnormalities consistent with MS. Treatment with omega-3 fatty acids, beta blockers, ACE inhibitors, estrogen, and meditation may have a beneficial effect on insulin receptors and ventromedial hypothalamic dysfunction. However, no definite or precise insight into the pathophysiological link between MS, brain function and nutrition is available. Despite this, epidemiological studies and intervention trials indicate that treatment with n-3 fatty acids may be adopted in clinical practice and used to direct therapy for prevention of type 2 diabetes, hypertension, coronary artery disease (CAD), and atherosclerosis, thereby indicating that MS may also respond to this treatment. - Objective: To study the effect of medroxyprogesterone acetate (MPA) on autonomic cardiac control in respiratory insufficiency in postmenopausal women. - Design: A prospective, single-blind study. - Subjects: Eighteen postmenopausal women with respiratory insufficiency and eight asymptomatic postmenopausal women with nocturnal hypoxaemia as controls. - Methods: Oral MPA treatment was given at 30 mg twice daily for 2 weeks. All-night polysomnography including a two-channel electroencephalogram, an electro-oculogram, an electromyogram, an electrocardiogram, arterial oxyhaemoglobin saturation, maximum end-tidal CO2 partial pressure, a ballistocardiogram and breathing movemen...